PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP TURNOVER INTENTION PADA KARYAWAN PT. GANDA BUANINDO KUANTAN SINGINGI HILIR - Nova Ade Perdana; Machasin -; Marhadi - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to analyze the effect of partial and simultaneous variables job satisfaction and organizational commitment on the turnover intention of employees of PT. Ganda Buanindo. The study was conducted January 12, 2014 until July 22, 2014. In this study consists of three variables: the dependent variable and two independent variables. These variables are Turnover Intention (Y), Job Satisfaction (X1) Organizational Commitment (X2). The study was conducted using a sample of 96 people. Research using census techniques by giving questionnaires to the respondents. In terms of data analysis, research using qualitative methods and quantitative methods with SPSS (Statistical Package for Social Science) version 20.0.Unknown variables of job satisfaction and organizational commitment on turnover intention of employees of PT. Ganda Buanindo simultaneously and negative partially. Variables are the dominant influence on the turnover intention of employees of PT. Ganda Buanindo is job satisfaction. Thus it can be interpreted that the variable job satisfaction and organizational commitment negatively affect employee turnover intention at PT. Ganda Buanindo. So by increasing job satisfaction and organizational commitment of the employees are able to reduce the level of employee turnover intention at PT. Ganda Buanindo.Keywords: Job Satisfaction, Organizational Commitment, Turnover Intention